Whose city? What politics? Contentious and non-contentious spaces on Colorado's Front Range. (November 2015) - Mitchell, Don; Attoh, Kafui; Staeheli, Lynn
Drawing on research from Colorado's Front Range (the Denver/Boulder metropolitan area), this paper examines the validity of the 'post-political' hypothesis for explaining contentiousness and non-contentiousness in urban space. Examining major urban redevelopment efforts in Denver and a controversy over homeless people sleeping in public space in Boulder, we suggest that the literature on post-politics too narrowly circumscribes the realm of political action and in so doing loses analytical force and risks misunderstanding the nature of political engagement in the city. By contrast, a less circumscribed, more supple definition of politics allows for a better understanding of how the question of 'Whose City?'– who the city is for – is always up for grabs. The appearance of post-political consensus, when it occurs, is itself a political achievement, the making of a hegemony, not an explanation.